Global improvements of a protein alignment algorithm and comparison with a global optimization solver - Paulo Gouveia; Roberto Andreani; Ana Friedlander; Jose Mario Martínez; Leandro Martínez (Bulletin of Computational Applied Mathematics, 2013)
The LovoAlign method for Protein Alignment, based on the Low-Order Value Optimization theory, is recalled. The method is modified in order to improve global convergence properties and compared against other global minimization procedures.